2002
DOI: 10.1007/s00442-001-0857-5
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific differences in cuticular hydrocarbon profiles of Myrmica ants are sufficiently consistent to explain host specificity by Maculinea (large blue) butterflies

Abstract: The chemical signatures on the cuticles of five common Myrmica ant species were analysed (49 colonies of M. rubra, M. ruginodis, M. sabuleti, M. scabrinodis and M. schencki), each ant being the specific host of one of the five threatened European species of Maculinea butterfly. The cuticular hydrocarbon profile (based on the relative abundance of each chemical) of each ant species was highly distinctive, even between the morphologically similar species M. sabuleti and M. scabrinodis. There was no significant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
84
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(93 citation statements)
references
References 42 publications
6
84
3
Order By: Relevance
“…After spending 10-15 days feeding on a species-specific food plant, Maculinea larvae drop to the ground and wait until they are found and carried into an ant nest by a Myrmica worker (Elmes et al 1991a;Akino et al 1999;Elmes et al 2002;Thomas 2002). Adoption of the parasite caterpillars by the host ants is mediated by chemical deception (Akino et al 1999;Schönrogge et al 2004;Nash et al 2008;Fürst et al 2011).…”
Section: The Case Of Maculinea Butterfliesmentioning
confidence: 99%
See 1 more Smart Citation
“…After spending 10-15 days feeding on a species-specific food plant, Maculinea larvae drop to the ground and wait until they are found and carried into an ant nest by a Myrmica worker (Elmes et al 1991a;Akino et al 1999;Elmes et al 2002;Thomas 2002). Adoption of the parasite caterpillars by the host ants is mediated by chemical deception (Akino et al 1999;Schönrogge et al 2004;Nash et al 2008;Fürst et al 2011).…”
Section: The Case Of Maculinea Butterfliesmentioning
confidence: 99%
“…By contrast, caterpillars adopted within nests of other Myrmica species suppress their secretions and rely on the passive acquisition of their current host colony odour ). Acquired camouflage alone, however, is an insufficient mechanism to survive periods of stress or deprivation inside the colony, when worker ants become more discriminating (Elmes et al 2002).…”
Section: Host Ants' Diversification In Maculinea Populationsmentioning
confidence: 99%
“…It is known that cuticular hydrocarbons play an important role, both during the initial as well as the full integration phase of cuckoo Maculinea larvae with their host ant species (Akino et al, 1999;Elmes et al, 2002;Schönrogge et al, 2004;. Schönrogge et al (2004) showed that M. 'rebeli' larvae reared by colonies of its primary host species use chemical mimicry by an active production of hydrocarbons in addition to those found on pre-adoption larvae (and not necessarily shared with the host), whereas larvae kept in nests of non-host species seem to acquire chemical compounds from ants.…”
Section: Discussionmentioning
confidence: 99%
“…Maculinea larvae first feed on specific food plants and in their final instar they are adopted by Myrmica workers and taken into ant colonies where they spend 11-23 months Schönrogge et al, 2000;Witek et al, 2006). It is known that Maculinea larvae are picked up and carried to nests by workers of any Myrmica species that encounter them (Elmes et al, 1991a(Elmes et al, , 2002Akino et al, 1999;Thomas, 2002). The next and more important step is 'initial integration' into the ant society which takes place within the first 24-48 h inside the colony.…”
Section: Introductionmentioning
confidence: 99%
“…The adoption of the caterpillars by ants is mediated by chemical deception (Akino et al, 1999;Schönrogge et al, 2004;Fürst et al, 2012). As it has been demonstrated in the case of the cuckoo butterflies, Maculinea alcon (cruciata ecotype) preadoption caterpillars synthesize a simple mixture of cuticular hydrocarbons (CHC) that weakly mimic those of Myrmica species in general, but that have the closest match to the hydrocarbon signature of their local host ant M. schencki (Akino et al, 1999;Elmes et al, 2002). Yet the low level of chemical similarity means that preadoption butterfly caterpillars could be retrieved by any foraging Myrmica species that happen to encounter it, and not just by M. schencki (Akino et al, 1999;Elmes et al, 2002;Schönrogge et al, 2004;Thomas et al, 2013) although in the laboratory adoption appears to be the most rapid with this local, main host ant species.…”
Section: Arnaldomentioning
confidence: 99%